The use of reperfusion therapy in transition countries without fully applicable pharmacoinvasive strategy - Krljanac Gordana; Ašanin Milika; Mickovski-Katalina Nataša; Milanović Slađan D.; Bjekić Jovana; Savić Lidija; Mitrović Predrag; Đurović Marina; Vasiljević Zorana (Vojnosanitetski Pregled)
Background/Aim. The pharmacoinvasive (PI) therapy is a recommended strategy in patients (pts) with ST elevation myocardial infarction (STEMI) unable to undergo timely primary percutaneous coronary intervention (p-PCI). The aim of the study was to find out the cohorts of pts who are not treated by any reperfusion therapy (RT) as well to determine the outcome of the pts treated with RT in a transition country without fully applicable PI therapy. Methods. The study analyzed data from the Hospital National Registry for Acute Coronary Syndrome of Serbia (HORACS). Results. The significant predictors of the withdrawing of the application of any RT in the model [c 75.6%, SE 0.004, 95% CI 0.748–0.761)] were a ge ( ≥ 6 5 years), heart failure (Killip II-IV), diabetes mellitus, and the time to first medical contact (FMC) (> 360 min). In patients without RT, mortality was 15.7%, in pts treated with fibrinolytic therapy (FT) was 10.5%, and in pts treated with pPCI, it was 6.2% (p < 0.000). Within 3 hours to FMC, higher in-hospital mortality was in FT pts (FT 8.7% vs p-PCI 4.3%). FT treated patients were older, had more comorbidities and heart failure (HF). However, after propensity score matching, in order to ad-just the differences among the pts, the mortality rate remained higher in FT pts but not statistically significantly higher than in p-PCI pts (FT 8.8% vs p-PCI 6.4%). Conclusion. The balance of the best cost-benefit strategies for better use of RT is difficult to achieve in transition countries. The possibility for timely p-PCI and PI therapy is especially not applicable in high-risk patients, older pts, pts with HF, and those with diabetes mellitus.